Quick facts lung cancer : what you need to know--now - American Cancer Society (Atlanta, Ga. : American Cancer Society, 2007)
What are your risk factors for lung cancer? Can you prevent it? How is lung cancer treated? What should you ask your doctor? QuickFACTS Lung Cancer is both a comprehensive and a quick read, with highlighted cover tabs for quick reference of specific topics. QuickFACTS Lung Cancer: Covers everything from risk factors to living well after cancer treatment; provides critical questions to ask your healthcare team; educates and empowers you right from the start; completely updated with the latest patient treatment guidelines; includes a lung cancer dictionary.
Includes bibliographical references and index.
Keywords: Lungs -- Cancer -- Popular works